STRATEGI PENGADAAN ALUTSISTA PESAWAT UDARA CN235 PESAWAT PATROLI MARITIM SARANA PERTAHANAN INDUSTRI PERTAHANAN INDONESIA - Moeis Sya’ifudin; Hendro Yusworo (Media Bina Ilmiah, 2022)
Procurement of defense equipments has been a necessary needs in developing national defense systems. However, the cost needed for procuring such defense equipments is very costly. National defense industried has to take benefit from the defense equipment procurement programs in MOD. It requires national consensus that favors to the capacity building of national defense industries to gain competitive core competence in regional and global level. This consensus is conceptualized in optimizing cooperation among related entities that directly involved in defense systems procurement Aircraft CN235 Maritime Patrol Defense industries, especially Ministry of Defense, Indonesian Defense Forces, and local defense industriesin developing defense equipment systems that based on local defense industries.